THE EFFECT OF CHICKEN MANURE AND Potassium chloride ON THE GROWTH AND YIELD Abelmoschus esculentus of ALLUVIAL - SRIDEVI, GITA; SURACHMAN, SURACHMAN; warganda, warganda (Jurnal Sains Mahasiswa Pertanian, 2019)
This study aimed to determine the interaction between the use of organic chicken manure and Potassium chloride fertilizer which is better for growth and yield of Abelmoschus esculentus in alluvial soil. This research was conducted on November 20, to 2018 until January 23, to 2018 in Parit Lintang Village, Salatiga District, Sambas. This study used a Factorial experiment with a Randomized Block Design (RBD) which consists of 2 factors. The first factor of the doses used of manure chicken: a1 = gived chicken manure 5 ton / ha equivalent to 2.5 kg / plot, a2 = gived fertilizer chicken manure 10 ton / ha is equivalent to 4.5 kg / plot, a3 = giving chicken manure 15 ton / ha is equivalent to 6.5 kg / plot. The second factor of the doses Potassium chloride fertilizer: b1 = 100 kg / plot is equivalent to 87.5 g / plot, b2 = 150 kg / plot equals 131.3 g / plot, b3 = 200 kg / plot equals 333.33 g / plot. There were 9 combinations of treatment in this study, each treatment was repeated 3 times and each treatment consisted of 3 plant samples so that there were 27 experimental unit. The variables observed in this study include the leaf area (cm2), root volume (cm3), shoot up dry weight (g), root dry weight (g), number of fruit (g), weight of fruit (g), weight of fruit layout (g). The results showed that the treatment of chicken manure application and Potassium chloride fertilizer could increase the growth and yield of Abelmoschus esculentus plants in alluvial soil. Further, there was no interaction between the two treatment of chicken manure and Potassium chloride fertilizer. Chicken manure at 15 ton / ha treatment equivalent to 6.5 kg / plot and Potassium chloride fertilizer at 200 kg / plot treatment equivalent to 333.33 g / plot gave the highest yield. Keywords: Alluvial, Chicken Manure, Potassium chlorida , Abelmoschus esculentus